Additive manufacturing of NiTi-Ti6Al4V multi-material cellular structures targeting orthopedic implants - Bartolomeu, Flávio (2020)
The amount of hip revision surgeries is significantly increasing due to the loss of fixation between implant and bone, that leads to implant failure. The stiffness mismatch between Ti6Al4V hip implants and bone tissue, the non-uniform implant-bone contact pressure, and the poor wear resistance of Ti6Al4V are pointed as three critical issues that contribute to these implant's failure. In this study, a multi-material design and fabrication concept was exploited aiming to change traditional manufacturing paradigms, by allocating different biomaterials in a single component targeting a multi-functional hip implant. Selective Laser Melting technology was explored to fabricate NiTi-Ti6Al4V multi-material cellular structures with a Ti6Al4V inner region and a NiTi outer region. This work was focused on the SLM fabrication and processing parameters validation on a commercial SLM equipment. The morphological analyses allowed to assess a successful solidification and bond between NiTi and Ti6Al4V materials in the transition region. The shear tests revealed a high bond strength of the transition region with an average strength of 33 MPa. The nano-indentation results showed that the Ti6Al4V region exhibits a higher hardness and elastic modulus when compared with the NiTi region. This work is a part of a broader objective that aims to create a NiTi-Ti6Al4V multi-material and cellular structured hip implant capable to provide customized stiffness, superior wear resistance and a controlled NiTi outer region volume change.